Detecting schizophrenia in the prodromal phase: screening of genetic risk relatives - Salleh, Mohd Razali; Othman, Zahiruddin; Alwi, Muhd Najib Mohd; Yassin, Mohd Azhar Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Background: To screen and detect individuals at ultra high risk (UHR) for psychosis and evaluate the efficacy of a screening program. Methods: This a two-stage study involving relatives of patients with schizophrenia. The nonfirst degree relatives were additionally screened with the Screening Questionnaires ( SQ), besides the GHQ-12 and GAF in the first stage. All the positive subjects will proceed to the second stage assessment. Results: Sixty four (14.2 %) of 450 selective relatives were positive in the first stage. In the second stage, only 14 (3.1 %) were positive (UHR subject). The sensitivity of the SQ (67%) was much better than the GHQ (29%), but the specificity was not much difference. The d~t~ction rate of UHR individuals was higher in non-first degree relatives. Implications: Screening of genetic risk relatives is feasible. The high detection rate among non-first degree relatives is contributed by the addition of the SQ. The GHQ is not suitable for screening in early psychosis.